Pendidikan Pengetahuan Kesehatan Gigi dan Mulut pada Kader Posyandu Lansia di Wilayah Kerja Puskesmas Gondangrejo Karanganyar - Risya Cilmiaty; Adi Prayitno; Widia Susanti; Betty Saptiwi; Filumena Titis Rahutami (Abdimas Universal, 2023)
The elderly population in Indonesia is currently experiencing a significant increase, this shows that public awareness of health in general is getting better. However, with the increase in the elderly population, various problems will arise that affect aspects of the life of the elderly. One of the efforts made by the government in overcoming various problems in the elderly is to hold the Elderly Posyandu program. Dental and oral health in the elderly is one that needs special attention because it will affect general health. Good knowledge of oral hygiene is very important, so that it can prevent dental and oral diseases. To improve the quality of services primarily in the field of dental and oral health, this activity is specifically for the elderly. This service aims to improve the health of the elderly through posyandu cadres so that it will improve the quality of life and welfare for the elderly. The elderly Posyandu which is the target of dedication in this study is the elderly Posyandu which is located in the working area of the Gondangrejo District Health Center. There are 93 posyandu with 245 cadres spread throughout the sub-district. The method of dedication used is lectures and questions and answers, demonstrations, and simulations. The results of this service are expected to be useful for increasing Posyandu cadre resources which have an impact on improving the quality of elderly Posyandu services in the working area of the Gondangrejo Health Center, so that it will improve the health status of the elderly.